The Effect of Warehouse Layout on Work Productivity at PT Perkasa Primarindo - Ernawati ERNAWATI; Degdo SUPRAYITNO; Yuli EVITHA; Wahyuddin LATUNRENG (International Journal of Environmental, Sustainability, and Social Science, 2023)
The background of this research is the ineffective warehouse layout and the lack of utilization of storage space capacity in the warehouse so that it affects operational activities at the PT Perkasa Primarindo warehouse which results in less than optimal work productivity. This study aims to determine how much influence the warehouse layout has on work productivity at PT Perkasa Primarindo. According to Lambert (2011) warehouses are part of a company's logistics system that stores products in the form of (raw materials, parts, goods-in-process, and finished goods) at and between points of origin and points of consumption ( point-of-consumption), as well as providing information to management regarding the status, condition and disposition of stored items. Haming and Nurjamudin (2014) said layout is one of the operational strategic decisions that also determines the efficiency of the company's operations in the long term. Meanwhile, according to Burhanuddin and Yusuf (2016), work productivity is a measure that shows consideration between the inputs and outputs issued by the company and the role of the workforce owned by the unit of time, in other words measuring efficiency requires identifying the results of performance. This research uses quantitative research methods. The population in this study were PT Perkasa Primarindo's warehouse employees as many as 25 people and the sample in this study were 25 employees. Sampling in this study used the Non-Probability Sampling technique. The research location is at PT Perkasa Primarindo.